Rare presentation of systemic lupus erythematosus with idiopathic intracranial hypertension - Ang, Diana Lee Min; Adnan, Sitidalila; Hoo, Fan Kee (Pakistan Medical Association, 2018)
Idiopathic intracranial hypertension (IIH) is an extremely rare condition and rare in systemic lupus erythematosus (SLE). Herein we report a case of young lady presenting with increased intra-cranial pressure (ICP), normal neurological examination and imaging. She was diagnosed with IIH and responded well to steroid and cyclophosphamide. Meticulous clinical and laboratory assessment must be carried out in suspicious case to avoid misdiagnosis.